Exploring Multidimensional View of Intellectual Capital and Business Ethics on Organizational Performance by Using Bootstrapping Method: Evidence from Pakistani Pharmaceutical Industry - Rizwan Raheem Ahmed; Jolita Vveinhardt; Dalia Streimikiene (Montenegrin Journal of Economics)
The objective of this research is to examine the effect of business ethics (BE) and intellectual capital (IC) on the organizational performance (OP). In order to run this study, a conceptual model was designed based on the literature review, and the employees of the knowledge-based organization in pharmaceutical sector were surveyed using a closed-ended questionnaire. Modern successful and thriving organizations are those that create IC and convert it into applicable methods to improve their activities and performance within the boundaries of BE.